Experimental Method and Application of Rapid and Continuous Extraction of Reduced Inorganic Sulfur from Sediments - MAO Changping; DU Suming; JIA Zhimin; YU Gang; WANG Yao; RAO Wenbo (Yankuang ceshi, 2023)
BACKGROUND Sulfur is an active element with multiple chemical forms, which plays a vital role in the regulation of redox chemistry. Reduced inorganic sulfur (RIS) including acid volatile sulfur (AVS), elemental sulfur (ES) and pyrite sulfur (CRS) is the most active part of sulfur species in sediments and plays an important role in controlling the geochemical behavior of iron, phosphorus and heavy metals in sediments. Separation and determination of reduced inorganic sulfur in anoxic sediments are critical to ecological and geological studies of sulfur cycles.Both distillation and diffusion methods can be effectively used to separate AVS, ES, and CRS in sediments. However, the current methods for extracting sulfur species are difficult to adapt to the large number of samples in geological and environmental research. Due to the reaction time, requirements of 24h for single sulfur species in the diffusion method limits the number of samples that can be processed on a timely basis. This limitation presents a problem for analyzing fresh anoxic sediment samples which have to be processed immediately to minimize the risk of sulfide re-oxidation. The detection method has the disadvantages of having a cumbersome testing process, long analysis time, and easy loss of sulfur components. OBJECTIVES To achieve efficient and continuous determination of reduced inorganic sulfur forms in bulk sediment samples. METHODS The method used in this experiment was improved based on the thermal distillation method, which was used to continuously extract the reduced inorganic sulfur from sediments. The reaction flask used in the experiment was a three-head round-bottom flask. A nitrogen flushing pipe, a condenser tube and two injection tubes were connected to each of the small necks. For the AVS procedure, 1.00g sediment sample reacted with 10mL of 6mol/L HCl under nitrogen gas at an elevated temperature (90℃) to convert reduced sulfur species into hydrogen sulfide which was subsequently carried by a nitrogen gas stream into a trap. For the CRS procedure, 20mL of CrCl2 solution was added to the sediment in the distillation flask after the AVS procedure, and 10mL of 6mol/L HCl was immediately placed in the flask at an elevated temperature (90℃), flushed with nitrogen. For the ES procedure, 20mL DMF were poured into the sample flask which contained acid and CrCl2 solutions from the previous procedure. 20mL of CrCl2 solution and 10mL of 6mol/L HCl were injected into the flask, and the reaction was allowed to take place at 90℃ purging with nitrogen. During the entire distillation process, H2S gas was absorbed by NaOH solution, and then oxidized by H2O2 to SO42-. The concentrations of SO42- were obtained by ion chromatography. RESULTS Repeatability experiments (n=3) were conducted on sediment samples from the Three Gorges Reservoir area and the mean values of acid volatile sulfur, elemental sulfur and pyrite sulfur were obtained as 0.19, 0.37 and 3.10μmol/g, respectively. The relative standard deviations (RSD) of the experimental results were 5.26%, 1.22% and 3.09%, respectively. In order to test the effectiveness of the distillation procedures, Na2S·9H2O, pyrite and S were added in the sediment to reveal the corresponding standard recoveries. An average of 92.8% of the added Na2S·9H2O was recovered by the AVS diffusion method. An average of 93.6% of the added pyrite was recovered by the CRS diffusion method. An average of 94.1% of the added elemental sulfur was recovered by the ES diffusion method. In the literature, recovery of AVS by the improved diffusion method ranged from 82.01% to 108.71%, and recovery of ES ranged from 92.25% to 98.08% (n=3), respectively.The modified apparatus presented in this paper was an economic version which uses rubber and glass parts. The method provided the advantages of lower sample weighing, and simple operation. Compared with the diffusion method (24h), the extraction time for individual sulfur forms by our distillation method was just 1.5h. The recoveries achieved by the method are comparable to those reported for earlier methods. In addition, the results are more like the data on reduced inorganic sulfur content obtained by Hongbin Yin after measuring sediment samples from Taihu Lake using the modified cold diffusion method, indicating that the method designed in this study has a high degree of confidence.Geochemical processes of sulfur in river aquatic systems play a crucial role in environmental evolution. In this study, the distributions and seasonal variation of reduced inorganic sulfur (RIS) in the Three Gorges Reservoir area surface sediments were investigated. Surface sediment samples were collected from 8 points in the section from Yunyang to Zigui in the Three Gorges Reservoir area in August and December 2017. The result showed that the AVS and ES contents were higher in summer than in winter, and the trend of RIS in the section from Yunyang to Zigui was roughly decreasing, with obvious seasonal and spatial changes. Low sulfur pollution in the Three Gorges Reservoir area was observed. CONCLUSIONS The improved thermal distillation method and apparatus in this study have significant advantages in the extraction efficiency of reduced inorganic sulfur from sediments. The extraction time of this study for individual sulfur form is 1.5h, less than the diffusion method. The established analytical method has good precision and accuracy, which is suitable for investigation studies with large numbers of samples such as environmental research and geological surveys.